THE ROLE OF THE SPECIALIST OF PHYSICAL CULTURE AND SPORT IN REALIZING IDEOLOGICAL EDUCATION OF THE SCHOOLCHILDREN (EDUCATION IN THE 21ST CENTURY, 2023)
The article discusses the issues of ideological education of schoolchildren in the frame of physical culture and sport activity. In physical culture and sport wide possibilities are invested for realizing moral, patriotic, ideological education of younger generation.Aim of the research: to study possibilities and directions of the work of physical culture specialist in realizing ideological education of schoolchildren in the process of physical culture and sport activity.In the process of physical education solving problems of ideological education of schoolchildren are discussed in following directions: patriotic, moral, ideological political, legal.Ideological education of schoolchildren, formation of morality, ideology, patriotism, active civil position is realized in the system of school education both during the lessons of physical culture and extra curriculum work, and in the process of sport competitive activity.Analysis of scientific methodical literature on the researched problem allowed to underline some questions not researched fully: in modern conditions of society development it has been changed the demands for ideological education of schoolchildren, which entails need to review the system of preparing physical education personnel and ways to improve this process.The further researches will be directed to working out methodical approaches and pedagogical conditions, corresponding to the character of forming preparation of future specialists of physical culture and sport realizing ideological education of younger generation.
Keywords: ideological education, physical education, sport, specialists of physical culture.